2019
DOI: 10.1146/annurev-marine-010318-095106
|View full text |Cite
|
Sign up to set email alerts
|

Marine Metazoan Modern Mass Extinction: Improving Predictions by Integrating Fossil, Modern, and Physiological Data

Abstract: Evolution, extinction, and dispersion are fundamental processes affecting marine biodiversity. Until recently, studies of extant marine systems focused mainly on evolution and dispersion, with extinction receiving less attention. Past extinction events have, however, shaped the evolutionary history of marine ecosystems, with ecological and evolutionary legacies still evident in modern seas. Current anthropogenic global changes increase extinction risk and pose a significant threat to marine ecosystems, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 145 publications
0
34
1
Order By: Relevance
“…Our results highlight the importance of accounting for phylogeny and exposure duration. Especially when considering long-term trials, these effects are more in line with the warming-induced reduction in body mass observed during long-term rearing experiments [5] and over past extinctions [8]. Explicitly incorporating timescale may thus hold the key to resolve discrepancies between short-term trials, which do not always find evidence for oxygen limitation, and the results of long-term laboratory and field studies, which do suggest a role for oxygen limitation.…”
Section: Resultsmentioning
confidence: 73%
“…Our results highlight the importance of accounting for phylogeny and exposure duration. Especially when considering long-term trials, these effects are more in line with the warming-induced reduction in body mass observed during long-term rearing experiments [5] and over past extinctions [8]. Explicitly incorporating timescale may thus hold the key to resolve discrepancies between short-term trials, which do not always find evidence for oxygen limitation, and the results of long-term laboratory and field studies, which do suggest a role for oxygen limitation.…”
Section: Resultsmentioning
confidence: 73%
“…Our results highlight the importance of accounting for phylogeny and exposure duration. Especially when considering long-term trials these effects are more in line with the warming-induced reduction in body mass observed during long-term rearing experiments [5] and over past extinctions [8]. Explicitly incorporating time scale may thus hold the key to resolve discrepancies between short-term trials that do not always find evidence for oxygen limitation and the results of long-term laboratory and field studies that do suggest a role for oxygen limitation.…”
Section: Resultsmentioning
confidence: 79%
“…Investigation of individual-and population-level (e.g. abundance) traits has provided evidence for a good match between fossil and recent extinction risk [55], and newer studies support this claim [40,56,57].…”
Section: Addressing Specific Questionsmentioning
confidence: 97%
“…For example, several marine mass extinctions are likely the result of multiple stressors that today jeopardise modern marine systems: warming, ocean acidification and deoxygenation [45,49,68,69]. The mechanistic links bridging organismic physiology and deep-time palaeontology are beginning to emerge [57], and a closer collaboration among disciplines is clearly the way forward.…”
Section: Addressing Specific Questionsmentioning
confidence: 99%